2004
DOI: 10.1093/aob/mch198
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Colleters in Several Species of Simira (Rubiaceae)

Abstract: Few ultrastructural differences were noted among the three species. These secretory structures not only protect the shoot apex, but also have taxonomic importance below the genus level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
67
2
18

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 33 publications
6
67
2
18
Order By: Relevance
“…As claimed for polysaccharides, lipid compounds may help avoid water loss, in addition to prohibiting fungal and microorganism attack, since this hydrophobic substance lubricates the surface of young leaves and floral buds, (Fahn 1979;Thomas & Dave 1989;Thomas 1991;Evert 2006;Paiva 2009;Mayer et al 2013). Proteins have also been reported as a component of the secretion produced by colleters from a variety of different species (Thomas & Dave 1990;Klein et al 2004;Miguel et al 2006;González & Tarragó 2009;Mayer et al 2011;Dalvi et al 2013). Some authors have suggested that such proteins may provide additional protection from fungi and parasites (Miguel et al 2006;Vieira et al 2006;Mayer et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…As claimed for polysaccharides, lipid compounds may help avoid water loss, in addition to prohibiting fungal and microorganism attack, since this hydrophobic substance lubricates the surface of young leaves and floral buds, (Fahn 1979;Thomas & Dave 1989;Thomas 1991;Evert 2006;Paiva 2009;Mayer et al 2013). Proteins have also been reported as a component of the secretion produced by colleters from a variety of different species (Thomas & Dave 1990;Klein et al 2004;Miguel et al 2006;González & Tarragó 2009;Mayer et al 2011;Dalvi et al 2013). Some authors have suggested that such proteins may provide additional protection from fungi and parasites (Miguel et al 2006;Vieira et al 2006;Mayer et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Klein et al (2004) observed that the colleters of Simira pikia are distributed in a line at the base of the stipule, while the colleters of S. glaziovii form two triangles at the base of the stipule. Miguel et al (2006) observed that the colleters of three species of Bathysa are distributed at the base of the stipules.…”
Section: Introductionmentioning
confidence: 98%
“…De acordo com Th omas (1991), além da protoderme, células do meristema fundamental e do procâmbio podem estar envolvidas na formação de coléteres, sendo mais raros aqueles originados exclusivamente de células protodérmicas. Coléteres com origem mista foram descritos por Da Cunha & Vieira (1997), Klein et al (2004), Barreiro & Machado (2007) para espécies de Rubiaceae e por Appezzato-da-Glória & Estelita (2000) para espécies de Apocynaceae. Coléteres com origem exclusivamente protodérmica foram registrados por Paiva & Machado (2006a) em Hymenaea stigonocarpa (Fabaceae) e por Paiva & Martins (2011).…”
Section: Discussionunclassified
“…As referidas substâncias são comumente relatadas como fazendo parte da secreção produzida por coléteres de diferentes taxa (Kronestedt-Robards & Robards 1991; Th omas 1991; Appezzatoda-Glória & Estelita 2000; Rio et al 2002;Klein et al 2004;Paiva & Machado 2006a,b;Barreiro & Machado 2007), sendo geralmente a mucilagem o principal componente da secreção, conforme registrado nos coléteres de H. pernambucensis.…”
Section: Discussionunclassified
See 1 more Smart Citation